Interpretasi Deposit Uranium Berdasarkan Data Tahanan Jenis dan Polarisasi Terinduksi di Sektor Rabau Hulu - Haryanto, Dwi; Supriyanto, Supriyanto; Soetopo, Bambang; Karunianto, Adhika Junara (EKSPLORIUM, 2015)
Rabau Hulu area, Kalan, Kalimantan Barat is a potential area of uranium that has been explored in detail by various methods. Methods of resistivity and induced polarization can be applied in the exploration of uranium deposits in which its mineralization associated with sulphide minerals. Processing, analysis, and interpretation of resistivity and induced polarization data conducted in order to identify the distribution of uranium deposits and lithology of the rocks in the study area. Uranium deposits in the area Rabau Hulu is generally associated with sulphides, tourmaline and contained in favorable rocks. Symptoms of uranium mineralization encountered in other forms of irregular and uneven consists of uraninite, pyrite, chalcopyrite, pyrrhotite, molybdenite, and ilmenite minerals. Data acquisition using dipole-dipole configuration in an area of ​​approximately 36 hectares, 46 lines along + 425 m. Acquisition of induced polarization frequency domain data which the same points and lines with resistivity data. Data processing produces resistivity and metal factor values and subsequently made two-dimensional section. Determination of resistivity and induced polarization are done by correlated boreholes data with the results of data processing. Resistivity of uranium deposits zone worth less than 2,000 Ωm and the value of metal factor greater than 90 mho/m. Uranium deposit zone is expanding along with the depth. Uranium deposits distribution trending Southwestern-Northeast and shaped lens.